1998
DOI: 10.1159/000017097
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Findings in Twins Discordant for Alzheimer’s Disease

Abstract: Data from computed tomography (CT) scans of 12 twin pairs in which one partner had Azheimer’s disease (AD) and the other partner is cognitively intact were analyzed to study structural brain features associated with AD while controlling for familial factors. Visual ratings and analysis of quantified areas and volumes indicated that AD twins showed more dilation of temporal horns, lateral ventricles and third ventricle, and more atrophy of temporal lobes, particularly in the anterior temporal/perisylvian area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 26 publications
3
99
0
Order By: Relevance
“…However, Bariety et al [19]showed that detached podocytes undergo phenotypic changes and express macrophage-associated markers in idiopathic collapsing glomerulopathy, a histological variant of primary FSGS. Barisoni et al [20]reported a dysregulated podocyte phenotype including podocalyxin in collapsing idiopathic FSGS and HIV-associated nephropathy. Indeed, urinary podocytes in cases with FSGS were shown to lose other podocyte markers, such as C3b receptor or GLEPP1.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bariety et al [19]showed that detached podocytes undergo phenotypic changes and express macrophage-associated markers in idiopathic collapsing glomerulopathy, a histological variant of primary FSGS. Barisoni et al [20]reported a dysregulated podocyte phenotype including podocalyxin in collapsing idiopathic FSGS and HIV-associated nephropathy. Indeed, urinary podocytes in cases with FSGS were shown to lose other podocyte markers, such as C3b receptor or GLEPP1.…”
Section: Discussionmentioning
confidence: 99%
“…The factors which distinguish primary and secondary FSGS consist of: (1) absence of a disease which can cause FSGS, including, specifically, hypertension and reduced nephron mass at presentation; (2) the presence of GEC damage ultrastructurally prior to change in renal function; (3) the presence of a variety of circulating permeability factors which can induce proteinuria in experimental animals and cause immediate proteinuria in the transplanted graft, suggesting a soluble factor as a pathogenetic process, and (4) a high rate of recurrence in a transplanted kidney as opposed to other forms of FSGS [8, 9]. Morphologically, primary FSGS can be categorized into three forms [5, 10, 11]: (1) classic FSGS with segmental areas of hyalinosis and segmental glomerular collapse near the vascular pole associated with adhesions between the collapsed area and Bowman’s capsule; (2) ‘tip’ lesions with segmental collapse of capillary loops and GEC proliferation at the tubular pole of the glomerulus, and (3) ‘collapsing’ glomerulopathy associated with GEC proliferation, expansion of Bowman’s space, loss of classic podocyte phenotype and transdifferentiation of podocytes into macrophage-like cells [12, 13]. For reasons that are yet to be determined, these three varieties of primary FSGS have different clinical courses, with the ‘collapsing’ variety having a malignant course with renal failure within several years of onset, severe nephrotic syndrome and unresponsiveness to treatment.…”
Section: Primary Fsgsmentioning
confidence: 99%
“…Second, during the course of this model podocytes lose their characteristic to be normally stained by anti-podocalyxin Ab and they obtain a new marker of a diseased state, to be positively stained by OS-3. Barisoni et al [20]reported that podocytes lose their characteristic to be stained with anti-podocalyxin Ab in the diseased states such as collapsing focal segmental glomerulosclerosis (FSGS) and HIV-associated nephropathy. Interestingly, a site not stained with anti-podocalyxin Ab was demonstrated to correspond to the part positively stained with OS-3 in the serial section (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Parts of the crescent-forming cells have been suggested to be derived from podocytes with metaplastic changes [7, 10, 20]. Morita et al [7]concluded, from the morphological findings in human renal biopsies, that podocytes transform into crescent cells, light and dark cells, in a manner similar to that of PGEC.…”
Section: Discussionmentioning
confidence: 99%